Information technology use in Chinese firms and work-family conflict: The moderating role of guanxi. (August 2019) - Ma, Yanan; Turel, Ofir
Highlights: Guanxi is an important value in Chinese society and workplaces. Little is known about how guanxi interacts with modern digitization to influence work-family conflict. IT use for work increase work-family conflict. Peer guanxi reduces it. Supervisor-subordinate guanxi augments the effect of IT use for work on work-family conflict. There are gender differences in guanxi effects; they are more pronounced in men. Abstract: Modern Chinese firms are characterized by high digitization, as well as by traditional guanxi. It is unclear how these modern and old characteristics operate in tandem to influence employee outcomes. We make first strides toward bridging this gap by leveraging theories of interpersonal relationships (social exchange, leader-member exchange and interpersonal trust theories) to suggest that two types of guanxi, supervisor-subordinate guanxi and peer guanxi, can influence the translation of IT use for work into work-family conflict. Data from 485 employees in Chinese firms support most of our hypotheses, and show that: (1) IT use for work increases work-family conflict, (2) Peer guanxi reduces it, (3) supervisor-subordinate guanxi augments the effect of IT use for work on work-family conflict, and (4) there are gender differences in guanxi effects (for women, the effect of IT use for work on work-family conflict is consistent at different levels of supervisor-subordinate guanxi; for men this effect is augmented in high supervisor-subordinate guanxi conditions). Ultimately, the findings extend and provide a unique integration of old and new traditions in Chinese firms. The IT literature is extended by showing how guanxi can influence the translation of IT use for work into negative outcomes in the family domain. The guanxi literature is extended by showing how guanxi, which is largely perceived as positive, can have negative outcomes in form of strengthening the effect of IT use for work on work family conflict.